METHODOLOGY FOR ENGINEERING CALCULATION OF STABILITY COEFFICIENT AGAINST WHEEL CLIMBING ON THE RAIL - Kurhan, D. M.; Hubar, O. V.; Havrilov, M. O. (Science and Transport Progress, 2020)
Purpose. One of the indicators of the track and rolling stock interaction, non-observance of which can result in a traffic safety violation, namely to derailment, is a condition for ensuring stability against the wheel flange climbing onto the rail head. The aim of this work is to create a methodology for practical engineering calculation of the resistance coefficient against the wheel flange climbing onto the rail head. The described methodology will have complete information both from calculation formulas and from reference materials, to eliminate the need to attract additional sources and special software. Methodology. The main objective of the implementation of this purpose is to bring the calculation of horizontal forces to the engineering level. Due to the complexity of the interaction process between the track and the rolling stock and the need to take into account a large number of factors that have an effect on the result, as a rule, complex dynamic models are used to determine horizontal forces. A possible solution lies in the assumption that for a specific type of rolling stock, the horizontal force can be calculated by linear dependence on the value of the unbalanced acceleration. For this, an analytical technique for calculating horizontal forces was used. Findings. The authors determined the missing coefficients for calculating the horizontal force depending on the unbalanced acceleration for some types of shunting locomotives and for a freight car taking into account its load level. Originality. In the work, scientific and practical approaches for the interaction analysis of the track and rolling stock in the horizontal plane acquired further development. Practical value. The proposed step-by-step methodology for calculating the stability coefficient makes it possible at the engineering level to carry out a practical analysis of ensuring the safety margin against the wheel flange climbing onto the rail head, which is necessary when investigating the causes of rolling stock derailment and for a number of other tasks related to movement in curved track sections.